Avaliação do potencial terapêutico e da toxicidade das sementes de Bixa orellana L. no tratamento de dislipidemias - Ferreira, Jamile Magalhães (2010)
Bixa orellana seeds have been used widely in food and cosmetic industry, besides being used popularly to treat various pathological disorders. The aim of the present work was to evaluate the toxicity and the therapeutical potential of the aqueous suspension of Bixa orellana (ASBO) seeds in the treatment of dyslipidemia. For all experimental protocols, ASBO was utilized in the doses of 200mg/kg (ASBO 200), 400mg/kg (ASBO 400) and 800mg/kg (ASBO 800), save in the up-and-down test for which doses of 2000 and 5000mg/kg were used. Toxicological evaluation of repeated doses was carried out with a single daily oral administration during 30 and 90 days. Study of ASBO effect on the lipid metabolism was developed using mice with dyslipidemia induced by triton WR-1339, ethanol, hypercaloric diet and poloxamer- 407 (P-407). This last hyperlipidemia protocol was chosen in order to analyze the hexanic (HX), chloroformic (CLO), ethil acetate (EA) and n-buthanolic (N-BUT) fractions obtained from ASBO. Moreover, ASBO and CLO were studied in a protocol of hypercaloric diet. Toxic signals were not noted in the up-and-down test after ASBO administration. In the repeated doses toxicity protocol ASBO determined alterations in some biochemical parameters such as glycemia, levels of AST, ALT and of alkaline phosphatase; however, statistically significant differences were not verified as to the hemogram of the groups studied. ASBO treatment in the doses studied promoted a significant reduction of triglycerides (TG) in 24h and 48h, after triton (400mg/kg) intraperitoneal injection. 400 and 800mg/kg ASBO reduced TG serum levels of animals with hypertriglyceridemia induced by 10% and 26% ethanol. In the poloxamer 407 (1000mg/kg) protocol the administration of 200 ASBO, 400 ASBO and 800 ASBO provoked relevant reduction of TG values in 24h, 48h and 72h. Still in the last hyperlipidemia experimental model, HX, CLO, EA and N-BUT fractions revealed to exert a hypolipidemic effect at 72h. In regard to the hypercaloric diet protocol, ASBO in all doses tested, as well as CLO 3 promoted a decrease in total cholesterol (TC) levels. AST levels were raised in CLO 1, 2 and 3. In conclusion, Bixa orellana seeds, in the preparation evaluated in the present work have not shown toxic characteristics, for the studied periods. Moreover, ASBO and its chloroformic fraction seem to possess hypolipidemic activities. The results are promising and suggest therapeutical potentialities as well as safety in the application of this suspension in the treatment of dyslipidemia; however other pre-clinical and clinical studies with B. orellana seeds are necessary to assess their real therapeutical applicability.